Curvelet-Based Synthetic Aperture Radar Image Classification - Uslu, Erkan; Albayrak, Songul (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2014)
Curvelet transform (CT) is a multiscale directional transform that enables the use of texture and spatial locality information. In synthetic aperture radar (SAR) imaging, CT is mostly used in speckle noise reduction. This letter utilizes CT for feature extraction in land use classification. Two types of curvelet-based feature extraction methods are implemented for SAR. The first one is defined and used in content-based image retrieval and is based on generalized Gaussian distribution parameter estimation for each curvelet subband. The second implementation is a genuine method that utilizes the use of curvelet subband histograms, namely, histogram of curvelets (HoC). Using the proposed curvelet-based feature extraction method (HoC) on SAR data, better classification accuracies up to 99.56% are achieved compared to original data and H/A/alpha decomposition features. Compared to speckle-noise-reduced data classification results, it can be said that curvelet-based feature extraction is also robust against speckle noise.
Keywords: Curvelet transform (CT); generalized Gaussian distribution (GGD); histogram of curvelets (HoC); land use classification; synthetic aperture radar (SAR); Geochemistry & Geophysics; Engineering; Remote Sensing; Imaging Science & Photographic Technology